2019
DOI: 10.1097/qai.0000000000002142
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Adherence Level Necessary for HIV Viral Suppression Using Real-World Data

Abstract: Background: A benchmark of near-perfect adherence (≥95%) to antiretroviral therapy (ART) is often cited as necessary for HIV viral suppression. However, given newer, more effective ART medications, the threshold for viral suppression may be lower. We estimated the minimum ART adherence level necessary to achieve viral suppression. Settings: The Patient-centered HIV Care Model demonstration project. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
118
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(133 citation statements)
references
References 29 publications
7
118
3
5
Order By: Relevance
“…However, despite the increased availability of antiretroviral medications, HIV-related morbidity, mortality, and new infection rate continually increased over the years in China from 2004 to 2016 [1]. Both clinical trials and cohort studies have shown that the effectiveness of antiretroviral medications is highly dependent on adherence [2][3][4]. Suboptimal adherence severely undercuts antiretroviral effectiveness and places PLHIV at risk for virologic failure, increases the risk of onward HIV transmission, and limits the impact of HIV treatment resources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the increased availability of antiretroviral medications, HIV-related morbidity, mortality, and new infection rate continually increased over the years in China from 2004 to 2016 [1]. Both clinical trials and cohort studies have shown that the effectiveness of antiretroviral medications is highly dependent on adherence [2][3][4]. Suboptimal adherence severely undercuts antiretroviral effectiveness and places PLHIV at risk for virologic failure, increases the risk of onward HIV transmission, and limits the impact of HIV treatment resources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The UNAIDS 90-90-90 goals map the HIV care cascade in terms of knowledge of HIV status, sustained receipt of antiretroviral therapy (ART) and attainment of viral suppression [2]. The second and third '90s' are highly dependent on adherence [3,4]. Adherence to ART involves a number of components along the HIV care cascade, namely linking with care to initiate treatment, the need for ongoing engagement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This scoping review discusses strategies to improve adherence for five target populations along five components of the HIV treatment cascade: (1) PLHIV who know their status and are not yet initiated on ART, (2) all PLHIV prescribed ART, (3) ART users with sub-optimal adherence, (4) ART users with stable adherence and (5) PLHIV initiated on treatment who disengage from care for periods of time or are lost to follow-up (LTFU). Within these categories, we make a special note of populations facing unique challenges, such as youth, pregnant women and those with common mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence in the country has shown that only 32% of PLWHA on ART have suppressed viral loads ( UNAIDS, 2017 ). Studies have indicated that lack of viral suppression is an indication of non-adherence to ART ( Byrd et al, 2019 ; Nasuuna et al, 2018 ; Robbins et al, 2014 ). Therefore, understanding the level of adherence and factors related with non-adherence helps to prevent the future threat of widespread treatment resistant HIV strains.…”
Section: Introductionmentioning
confidence: 99%